KOMUNIKASI POSITIF PENDIDIK PAUD DALAM PEMBELAJARAN BAHASA ANAK USIA DINI - Muzaqi, Moh. (JIV-Jurnal Ilmiah Visi, 2009)
Language as a means of education is very important in developing the attitude of early age children. The choice of words and the language style used in communication can give psychological effects to the children as they are still very sensitive. This article put forwards the negative effects of inappropriate language (negative language) used by the teachers or parents to communicate with the children. Having discussed critically the inappropriate words, phrases, and sentenses for the children of early age, the article propose words, phrases, and sentences (positive language) which can give positive effects to their development. To conclude the discussion, it recommends certain words, phrases, and sentenses to avoid and to substitut.